2023
DOI: 10.1039/d3cp01437a
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the reinforcing effect of a nanorod network on a polymer matrix through molecular dynamics simulations

et al.

Abstract: Controlling the spatial morphology of the nanorods (NRs) in polymer matrix and understanding the structure-property relationship are crucial for fabricating high-performance polymer nanocomposites (PNCs). By employing molecular dynamics simulations, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…In order to reveal the dynamics, energy, structure and performance of polymeric composites, [23][24][25][26] molecular dynamics (MD) simulation offers an effective way to investigate the interfacial interactions between fillers, the polymer matrix and compatibilizers. Zhang et al investigate the interfacial interactions between hydroxyapatite fillers and the PA matrix in the composites with and without compatibilizers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reveal the dynamics, energy, structure and performance of polymeric composites, [23][24][25][26] molecular dynamics (MD) simulation offers an effective way to investigate the interfacial interactions between fillers, the polymer matrix and compatibilizers. Zhang et al investigate the interfacial interactions between hydroxyapatite fillers and the PA matrix in the composites with and without compatibilizers.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, no systematic studies into the LC behavior of polymer grafted CNCs have been performed to date. While simulations of nanorod–polymer mixtures are now relatively widespread, very few simulations of polymer grafted nanorods exist, and it is only very recently that computational attempts have been made to understand their self-assembly. These studies have been so far limited to single molecules, , disordered thin films in which polymer grafting is noted to disrupt the LC ordering and bulk studies into mechanical properties, dispersion effects, , graft locations and extremely low grafting densities where single polymer chains are attached to the rod tip which are computationally less demanding and allow for their LC behavior to be explored. , In none of these studies, however, is LC like behavior observed, likely due to low effective aspect ratios of short rods grafted with long polymers, patchy grafting, or improper crystallization protocols used to grow LC phases.…”
Section: Introductionmentioning
confidence: 99%